Lowe syndrome oral findings: Case report. Issue 1 (April 2016) - Okawa, Rena; Naka, Shuhei; Saga, Kanae; Nakano, Kazuhiko
Abstract: Lowe syndrome is an X-linked recessive disorder characterized by anomalies of the eye, nervous system, and kidney, and caused by a mutation of the oculocerebrorenal gene ( OCRL1 ) on the X-chromosome. Dental manifestations are associated with rickets due to renal dysfunction. A 2-year-1-month-old boy with Lowe syndrome came to our clinic for consultation in regard to mobility of the primary mandibular incisors. Periapical radiograph findings showed alveolar bone absorption and a wide pulp chamber. Dental caries extending to the pulp was detected on the palatal side of the maxillary central incisors. We initially provided brushing and dietary habit instructions, and subsequently performed periodontal and dental caries treatments. Repeated periodontal therapy led to disappearance of mobility of the affected teeth at the age of 3Y3M.